2019
DOI: 10.1111/jace.16383
|View full text |Cite
|
Sign up to set email alerts
|

First principles predicting enhanced ductility of boride carbide through magnesium microalloying

Abstract: The low fracture toughness of strong covalent solids prevents them from wide engineering applications. Microalloying metal elements into covalent solids may lead to a significant improvement on mechanical properties and drastical changes on the chemical bonding. To illustrate these effects we employed density functional theory (DFT) to examine the bonding characteristic and mechanical failure of recently synthesized magnesium boride carbide (Mg3B50C8) that is formed by adding Mg into boron carbide (B4C). We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…The density functional theory (DFT) study on NiAl alloy has shown that its ductility can be improved by microalloying Cr, Mo, Ti, and Ga elements into the cleavage or slip planes . For superhard materials, it has been demonstrated in both experiment and theory that microalloying Mg and Si in B 4 C can improve its mechanical properties …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The density functional theory (DFT) study on NiAl alloy has shown that its ductility can be improved by microalloying Cr, Mo, Ti, and Ga elements into the cleavage or slip planes . For superhard materials, it has been demonstrated in both experiment and theory that microalloying Mg and Si in B 4 C can improve its mechanical properties …”
Section: Introductionmentioning
confidence: 99%
“…41 For superhard materials, it has been demonstrated in both experiment and theory that microalloying Mg and Si in B 4 C can improve its mechanical properties. [42][43][44][45] In this Article, we employed DFT simulations at the Perdew-Burke-Ernzerhof (PBE) functional level 46 to examine the mechanical properties of r-LiB 13 C 2 and how the nanoscale twins affect the mechanical properties. We first examined the single crystal r-LiB 13 C 2 and identified its elastic modulus and failure mechanism under pure shear and indentation stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Our studies of brittleness in B 4 C showed that cracking across grains leads to amorphization 24 and we showed that very small grains lead to grain boundaries that direct shear along these boundaries 28 . This was studied in depth in collaboration with Lasalvia 34 . Interestingly, we found that microalloying with Mg also leads to enhanced ductility 35 .…”
Section: Models For the Key Mechanisms In Boron Carbidementioning
confidence: 57%
“…28 This was studied in depth in collaboration with Lasalvia. 34 Interestingly, we found that microalloying with Mg also leads to enhanced ductility. 35 This has not yet been tested experimentally.…”
Section: Methodsmentioning
confidence: 75%
“…Several approaches, such as microalloying, [12][13][14][15][16] stoichiometry control, [17][18][19] and addition of a second phase, [20][21][22] have been proposed to mitigate amorphous shear band formation. For microalloying, both non-metal dopants (P 23 and Si 24 ), as well as metal dopants (Li, 14,15 Mg, 12,16 and Ti 13 ) may decrease amorphization in B 4 C. Both experimental and theoretical studies have suggested that boron enrichment is helpful to mitigate amorphization. [17][18][19] Moreover, the addition of the second phase, such as SiC 25 and TiB 2 26 has been shown to improve the fracture toughness of B 4 C. Among these approaches, grain-boundary (GB) engineering is promising.…”
mentioning
confidence: 99%